ANALISIS RELOKASI TANAH DAN HUBUNGANNYA DENGAN RENCANA TATA RUANG WILAYAH PASCA TSUNAMI DI KOTA BANDA ACEH - GADIZA REZKYKA PUTRI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhd. Yamin2. Edy Ikhsan3. Faisal Akbar Nasution In agrarian scope, land is a part of the earth called the earth surface. The disaster of tsunami taking place on December 26, 2014 in the capital of Aceh, Banda Aceh, has incapacitated all human’s life aspects including all infrastructures in the city.Therefore, the government relocated or resettled the victims of tsunami or earthquake to a safe area for permanent settlement. It is expected that they can undergo their life as before again or even better. The implementation of Spatial Planning of Banda Aceh after tsunami, with the areal development in the new settlement area for the tsunami victims who are relocated, there is a question about how actually the certainty of the title of their old land after relocation is. Keywords : Land, Relocation, Spatial Planning